Humanistic Counseling in Increasing the Independence of New Male Students at the Pesantren Kyai Syarifuddin Wonorejo Lumajang - Faisol, Ahmad (Risalatuna Journal of Pesantren Studies, 2024)
Pondok pesantren serve as comprehensive educational environments where caregivers, nyai (female religious leaders), administrators, and instructors collaborate to foster the development of students, particularly in cultivating the independence of new students. One of the approaches employed to support this goal is the application of humanistic counseling techniques. This study aims to: (1) examine the implementation efforts of humanistic counseling; and (2) evaluate the outcomes of this counseling approach in promoting student autonomy. A qualitative research method was employed, with data validity ensured through technique and source triangulation. The findings reveal that the implementation of humanistic counseling was conducted over three structured sessions. The first session focused on developing students’ self-awareness. The second session emphasized understanding personal freedom in learning activities. The third session aimed to foster a sense of responsibility for one's own learning process. As a result, students (counselees) demonstrated improved self-awareness and greater independence in managing their academic tasks.